A Synchronous Tumor (Colon Adenocarcinoma and Cecal Appendage Carcinoid): Clinical Case - Ramírez-Vázquez, José Luis; López-Bernal, Carlos Alberto; Rosas-Zamora, Alma Jocelyn; Hernández-Morán, Alan Alexis; Falcón-Cancino, Luis Arturo; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction: Synchronous tumors are those primary neoplasms that appear during the diagnosis of another primary neoplasm or in the following six months, with a frequency of 9.9 to 3.5%. The tumors of the cecal appendix constitute a heterogeneous group of neoplasms with variable evolution and prognosis; they represent a small part of all gastrointestinal neoplasms, around 0.5 to 1%. Add to this a synchronous tumor, which is rare; the coexistence of colon and appendix cancer is unusual. Clinical case: A 79-year-old male underwent surgery due to intestinal occlusion. With imaging studies with a presumptive diagnosis by simple tomography of a tumor in the transverse colon at the level of the hepatic flexure, colonoscopy shows 70% stenosis in said segment. Surgical intervention was performed, performing right hemicolectomy with the anatomopathological result that reported: conventional, moderately differentiated adenocarcinoma and a cecal appendix with a microscopic finding of carcinoid tumor. Discussion: In this case, a carcinoid tumor of the appendix is documented in men, despite being more frequent in women. However, the presence of a synchronous tumor occurs more frequently in men with a ratio of 2-4:1, in the ages between 20 and 29 years for primary tumors and between 40 and 70 years in the case of synchronous tumors. Conclusion: This pathology is essential because the frequency of neuroendocrine tumor neoplasms at the appendiceal level is not high, and its simultaneous association with colorectal adenocarcinoma makes them even more unusual.